EFFECT OF COGNITIVE APPRENTICESHIP INSTRUCTIONAL METHOD ON ACADEMIC ACHIEVEMENT OF MOTOR VEHICLE MECHANICS’ WORK STUDENTS IN TECHNICAL COLLEGES IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2026)
The study investigated the effect of cognitive apprenticeship instructional method on motor vehicle mechanics’ work (MVMW) students in technical colleges in Anambra State. A quasi-experimental pretest posttest non-equivalent research design was adopted for the study. The population consisted of 328 NTC II MVMW students and a sample size of 73 using purposive sampling technique. The instrument data collection was a Motor Vehicle Mechanics’ Work Achievement Test (MVMWAT) validated by three experts in MVMW and measurement and evaluation. A reliability coefficient of 0.74 of the MVMWAT was found using Kuder-Richardson 21 (K-R21) formula. Two research questions and two hypotheses guided the study. Mean and standard deviation were used to answer the research questions while the analysis of covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. Findings from the study among others revealed that the cognitive apprenticeship instructional method significantly improved students’ academic achievement more than the demonstration method. It was therefore recommended that cognitive apprenticeship should be adopted as a preferred teaching method among other recommendations with a view to improve students’ academic performance.
Keywords: Motor Vehicle Mechanics’ Work; Cognitive Apprenticeship; Demonstration Method; Academic Achievement; Technical College